Az 1956-os közigazgatási területbeosztási reformterv földrajzi kérdései - Hajdú, Zoltán (Tér és Társadalom, 1989)
The case of reforming the historical spatial breakdown of administration has been raised in Hungary as a scientific, as well an actual political, question from the 1870s. The post-1945 period, similarly to previous ones, produced a large number of administration reform concepts, but when the administration reform was actually introduced following the communist take-over in 1949, spatial stability, rather peculiarly, was given a high priority and the radical spatial reform was, in fact, postponed. A radical plan of establishing a spatial structure that would meet the needs of socialist development was formulated as soon as 1953 but due to the evolving political crisis it was struck off the agenda. A period of corrections, full of contradictions itself, started in Hungarian political development in the summer of 1954 when a critical evaluation of existing structures was begun. The whole set of problems related to administration was reviewed within this context. Preparations for reforming the spatial breakdown of administration began in the automn of 1955. At the beginning, only the most restricted circle of the central party apparatus, then the state administration, and finally the representatives of science were involved in this job. The author provides a detailed analysis of the historical process of the formation of the political and scientific components of the spatial reform concept and the transformation of local ideas. Central spatial reform plans came across strong oppositions of county party- and council administrations; some counties responded with counter-concepts that was inconceivable earlier. The situation got particularly hot in Csongrád, Vas and Veszprém counties. The intention to reduce the area of Greater-Budapest created by the 1949 reform represented a special political problem. The leaders and the population of the settlements sanctioned for being detached condemned this intention extremely bitterly, they did not wish to become again ’villagers’ from ’capital-dwellers’. As a result of the deepening internal political crisis, from the summer of 1956, the possibility and the necessity of putting the reform into practice was debated even within the party leadership. At the beginning of October 1956, following sharp debates, the party leaders decided not to introduce the reform plan elaborated for approval to the Parliament, its realization would be postponed. The insurrection of 1956, then its suppression, created a new situation. The problems and tasks of the so-called consolidation came to the front, that needed stable administration organization and spatial breakdown. From the beginning of the 1960s, some elements of the reform plan of 1956 were put into practice while some others got off the agenda definitely.